THE IMPACT OF ACCOUNTING INFORMATION ON INVESTOR CONFIDENCE IN UGANDA: A CASE STUDY CARRIED OUT IN NAMANVE INDUSTRIAL PARK - PEACE ESTHER NAMUGAYA (UGANDA CHRISTIAN UNIVERSITY, 2025)
The main aim of the study was to establish the impact of accounting information on investor confidence, a case study that was carries on SME’s in Namanve Industrial Park.it was guided by the following objectives: to measure the extent to which accounting regulations contribute to maintaining investor confidence, assessing the impact of transparency in accounting information on investor decisions and evaluate the level of confidence investors place in audited accounting information. In the study, quantitative data was obtained with a total of 100 respondents including: SME owners, managers, investors and accountants. The findings reveal that opinions of accounting regulations, transparency and audits boost investor confidence. It was therefore concluded that accounting information affects investor confidence in Uganda.
Undergraduate Research
Keywords: undergraduate thesis